Management of COVID-19 During Lockdown and Reopening of Schools: An Experience Case under COVID-19 in Portugal - Martins, António Santos (Archives of Business Research, 2022)
The COVID-19 pandemic had a disruptive impact on educational institutions, around the world, during the lockdown and after the reopening of the schools. This unprecedented creates big challenges posed to educators, learners and schools to mitigate the effects of the pandemic. This investigation, supported by a questionnaire, tries to measure the satisfaction of the students, of a Higher-Level Public Education Institution – Guarda Polytechnic (IPG), Portugal, with the measures adopted to control the spread of the COVID-19 pandemic and propose some improvement suggestions. Although students refer that were satisfied with the arrangement of online classes during the lockdown of the IPG, they recognize that online classes affect negatively the academic performance and prefer face-to-face classes. In particular, female and older students, students that attend the Master’s degrees and students who have been attending the institution for 1 year or less are more satisfied with the overall management of the pandemic.